2013
DOI: 10.1161/circimaging.113.000438
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Fibrosis as a Key Determinant of Left Ventricular Remodeling in Idiopathic Dilated Cardiomyopathy

Abstract: Background-In idiopathic dilated cardiomyopathy, there are scarce data on the influence of late gadolinium enhancement (LGE) assessed by cardiovascular magnetic resonance on left ventricular (LV) remodeling. Methods and Results-Fifty-eight consecutive patients with idiopathic dilated cardiomyopathy underwent baseline clinical, biohumoral, and instrumental workup. Medical therapy was optimized after study enrollment. Cardiovascular magnetic resonance was used to assess ventricular volumes, function, and LGE ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
110
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 44 publications
9
110
0
1
Order By: Relevance
“…Fibrosis has been regarded as a marker of disease severity, reflecting the burden of initial myocardial damage and subsequent injury because of adverse LV remodeling. 23 However, there are cumulating evidences supporting the knowledge that fibrosis is not a fixed marker of disease severity 24 but rather a dynamic process that may play a causative role in the progression of LVSD and ensuing onset of CHF. 25 Currently, risk stratification in patients with preclinical LVSD is primarily based on the degree of LVSD in the view of the fact that the likelihood of CHF and death augments with increasing the degrees of LVSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrosis has been regarded as a marker of disease severity, reflecting the burden of initial myocardial damage and subsequent injury because of adverse LV remodeling. 23 However, there are cumulating evidences supporting the knowledge that fibrosis is not a fixed marker of disease severity 24 but rather a dynamic process that may play a causative role in the progression of LVSD and ensuing onset of CHF. 25 Currently, risk stratification in patients with preclinical LVSD is primarily based on the degree of LVSD in the view of the fact that the likelihood of CHF and death augments with increasing the degrees of LVSD.…”
Section: Discussionmentioning
confidence: 99%
“…1,28 Risk stratification based on LV ejection fraction is also limited by the fact that more than one third of patients with NICM experiences a consistent and sustained improvement of LV ejection fraction after optimization of medical therapy irrespective of the severity of initial LV dilatation and dysfunction. 24,29 Thus, effective risk stratification remains challenging in NICM particularly in subjects without history of CHF also because of the paucity of the data in this specific subgroup of patients. A remarkable finding of our study is that the addition of presence or extent of LGE to clinical data alone or in combination with parameters of LV remodeling and function significantly improved the outcome prediction.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In 7 explanted idiopathic dilated cardiomyopathy hearts, Gulati et al 4 showed an excellent agreement between replacement fibrosis at histopathology and LGE as seen with in vivo cardiovascular magnetic resonance. In our study, 5 we disregarded spotty LGE confined to the interventricular septum insertion points because whether this pattern identifies areas of fibrosis remains a matter of debate. For these reasons, we think that LGE in our patient population likely reflected replacement fibrosis.…”
Section: E79mentioning
confidence: 99%
“…1 We have recently shown in 502 patients with DCM that LV dilatation is correlated with increased wall stress, which precedes the development of LV hypertrophy. 4 Because the ensuing hypertrophy is still inappropriate, greater dilatation is associated with wall stress increase.…”
Section: E77mentioning
confidence: 99%
“…Applying these findings to the referenced study, it has to be inferred that at time of enrollment LV wall stress was markedly increased in patients responding to initiation or intensification of heart failure treatment with a favorable remodeling, which is also reflected by the fact of increased N-terminal pro-brain natriuretic peptide as reported. 1 Brain natriuretic peptide correlates with ventricular wall stress. 5 Based on the reported LV mass and volume and using the wall stress index, it has to be assumed that LV end-diastolic and end-systolic wall stress was increased to 4.9 kPa versus 4.6 kPa (end-diastolic LV pressure assumed at 16 mm Hg, normal end-diastolic wall stress <4 kPa) and to 28.0 kPa versus 21.0 kPa (peripheral systolic pressure inserted as reported, normal endsystolic wall stress <18 kPa), respectively.…”
Section: E77mentioning
confidence: 99%